Profile of Problem-based Learning (PBL) Model Assisted by PhET to Improve Critical Thinking Skills of High School Students in Dynamic Electrical Materials - Nabila Rahmadita; Husni Mubarok; Binar Kurnia Prahani (Jurnal Penelitian Pendidikan IPA, 2021)
This study discusses the implementation of problem-based learning (PBL) assisted by physics education technology (PhET) as a virtual laboratory to improve the critical thinking skills of high school students on dynamic electrical materials. The purposes of this research were to obtain the profile of students' critical thinking skills and the implementation of PBL assisted by PhET in senior high schools. This research method was a preliminary study with a qualitative descriptive analysis, written tests, student response questionnaires, and teacher interviews. The finding of students' critical thinking skills was categorized into three levels (low, moderate, and high). There are seventeen students in the low category, fifty-three students in the moderate category, and thirty students in the high category. The conclusion of this study revealed that students' critical thinking skills at the senior public school Surabaya were in the moderate category, and training questions were needed to improve students' critical thinking skills